2021
DOI: 10.1007/978-3-030-81111-2_16
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review on Virtual Reality Authentication

Abstract: As virtual reality (VR) sees an increase in use in several domains such as retail, education, military; a secure authentication scheme for VR devices is necessary to keep users' personal information safe. A smaller section of research focuses on the authentication schemes of VR devices. To further the understanding of this topic, we conducted a detailed literature review of VR authentication by exploring papers published till October 2020. A total of N = 29 papers were found. While many papers evaluate the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In the next level of full-text screening, we applied the eligibility criteria and further excluded 89 items. Five items were eligible according to our criteria, but were already included in a previous review by Jones et al (2021) which was also one of the selected papers. To avoid repetition, we did not include these items.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the next level of full-text screening, we applied the eligibility criteria and further excluded 89 items. Five items were eligible according to our criteria, but were already included in a previous review by Jones et al (2021) which was also one of the selected papers. To avoid repetition, we did not include these items.…”
Section: Resultsmentioning
confidence: 99%
“…User authentications are the key to combating identity theft and achieving secured identity management. In their review of virtual reality authentication, Jones et al (2021) identified and provided a comprehensive overview of 29 papers until October 2020. They categorized the authentication methodologies of selected works into four types: knowledge-based authentication, biometric authentication, multi-model authentication and gaze-based authentication.…”
Section: User Authenticationmentioning
confidence: 99%
See 1 more Smart Citation
“…From Table 2, it can be seen that not many [34][35][36][37][38][39][40][41] existing surveys discussed authentication methods in both AR and VR environments. In recent work by [34][35][36][37], authors focused on surveying miscellaneous methods of authentication.…”
Section: Refmentioning
confidence: 99%
“…From Table 2, it can be seen that not many [34][35][36][37][38][39][40][41] existing surveys discussed authentication methods in both AR and VR environments. In recent work by [34][35][36][37], authors focused on surveying miscellaneous methods of authentication. Stephenson et al [34] systematized authentication methods in both AR and VR based on properties concluded from user experience studies and interviews [42].…”
Section: Refmentioning
confidence: 99%